Infliximab for the treatment of CNS sarcoidosis: A multi-institutional series. (14th November 2017) - Gelfand, Jeffrey M.; Bradshaw, Michael J.; Stern, Barney J.; Clifford, David B.; Wang, Yunxia; Cho, Tracey A.; Koth, Laura L.; Hauser, Stephen L.; Dierkhising, Jason; Vu, NgocHanh; Sriram, Subramaniam; Moses, Harold; et al.
Abstract : Objective: To describe clinical and imaging responses in neurosarcoidosis to infliximab, a monoclonal antibody against tumor necrosis factor–α. Methods: Investigators at 6 US centers retrospectively identified patients with CNS sarcoidosis treated with infliximab, including only patients with definite or probable neurosarcoidosis following rigorous exclusion of other causes. Results: Of 66 patients with CNS sarcoidosis (27 definite, 39 probable) treated with infliximab for a median of 1.5 years, the mean age was 47.5 years at infliximab initiation (SD 11.7, range 24–71 years); 56.1% were female; 62.1% were white, 37.0% African American, and 3% Hispanic. Sarcoidosis was isolated to the CNS in 19.7%. Using infliximab doses ranging from 3 to 7 mg/kg every 4–8 weeks, MRI evidence of a favorable treatment response was observed in 82.1% of patients with imaging follow-up (n = 56), with complete remission of active disease in 51.8% and partial MRI improvement in 30.1%; MRI worsened in 1 patient (1.8%). There was clinical improvement in 77.3% of patients, with complete neurologic recovery in 28.8%, partial improvement in 48.5%, clinical stability in 18.2%, worsening in 3%, and 1 lost to follow-up. In 16 patients in remission when infliximab was discontinued, the disease recurred in 9 (56%), typically in the same neuroanatomic location. Conclusions: Most patients with CNS sarcoidosis treated with infliximab exhibit favorable imaging and clinical treatment responses, including some previously refractory to other immunosuppressive treatments. Classification of evidence: This study provides Class IV evidence that for patients with CNS sarcoidosis infliximab is associated with favorable imaging and clinical responses.